Design and implementation of a proportional integral controller in controller industrial process - Vargas Tamani, Bruno (2010)
This paper presents a methodology for designing a strategy proportional integral controller (PI) given that the policy will be implemented in an industrial process controller. The design considers the modeling of the plant through analog techniques of system identifi cation. It is used in controller design algorithm discrete digital PI controller that is running the process controller used. Considered for the design specifi cations of closed loop time response primarily to obtain a settling time line that you can be met without exceeding the range of the control signal that can deliver the process controller used. Implement the control system to verify the behavior of the closed loop system in relation to the specifi ed control objective.